Atoms and Subtle matter: Henry Power’s observations on plants in Experimental Philosophy - Matei, Oana (Notes and records of the Royal Society of London, 2025)
This paper examines Henry Power’s Experimental philosophy and suggests that Power’s observations of and experiments with plants were not used to reconcile Cartesian corpuscularianism with different approaches that stress the subtle character of matter. Instead, their purpose was rather to determine the nature of seeds and their role in the process of plant generation, i.e. whether they are containers of the ultimate division of matter (atoms) or parts of matter endowed with formative power. My argument starts with a discussion of Power’s presentation on the role of seeds in the process of plant generation in his Experimental philosophy . I claim that Power compares plant seeds to atoms, and that he does not strictly interpret seeds/atoms in the Cartesian corpuscularian and mechanical fashion. Power’s ‘atoms’ are of two kinds—subtle and grosser—where the subtle has the property to trigger natural processes. Moreover, I interpret seeds as parts of matter endowed with creative properties as an addition to the preformist interpretation of Power’s position on plant generation.